DESCRIPTION OF CUSTOMS AND TRADITIONS IN SHIA COMMUNITIES (World Bulletin of Social Sciences, 2024)
This article describes information as to the customs and traditions of shia communities and their unique characteristics. Together with this, in this article gives information about Navruz holiday and the history of its origin, “Haft sin” table which is considered a tradition of Navruz holiday and its characteristics.